2020
DOI: 10.14444/7090
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Cervical Disc Arthroplasty: Long-Term Outcomes at 3 and 4 Levels

Abstract: Background: Multilevel cervical degenerative disc disease in 2 or more segments poses treatment challenges. Anterior cervical discectomy and fusion is a viable treatment option, but one with high rates of adjacent segment disease and pseudoarthrosis. Cervical disc arthroplasty (CDA) is approved by the US Food and Drug Administration for the treatment of 1-and 2-level cervical pathology, with established long-term safety and effectiveness. Limited evidence exists for CDA at more than 2 levels. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Joaquim and Riew 42 performed a meta-analysis for multilevel CDA and concluded that the literature supports this option. Gornet et al 43 reported on a retrospective series of 139 patients who had 3-or 4-level CDA with 7 years of follow-up, and demonstrated improved patient-reported outcomes and a low reoperation rate. According to the aforementioned reports, 3-or 4-level CDA is feasible for multilevel radiculopathy or myelopathy, with satisfactory outcomes.…”
Section: Indications For Multilevel Cdamentioning
confidence: 99%
“…Joaquim and Riew 42 performed a meta-analysis for multilevel CDA and concluded that the literature supports this option. Gornet et al 43 reported on a retrospective series of 139 patients who had 3-or 4-level CDA with 7 years of follow-up, and demonstrated improved patient-reported outcomes and a low reoperation rate. According to the aforementioned reports, 3-or 4-level CDA is feasible for multilevel radiculopathy or myelopathy, with satisfactory outcomes.…”
Section: Indications For Multilevel Cdamentioning
confidence: 99%
“…8 The VR-12 has been utilized in a broad variety of clinical settings and is increasingly being incorporated in spine literature. 12,34,35 As use of this valuable measure inevitably continues to grow, systematic, procedure-specific validation will be increasingly necessary.…”
Section: Role Of Vr-12 In Spine Surgerymentioning
confidence: 99%
“…Another retrospective study examined 139 cervical disc arthroplasties (116 three-level and 23 four-level). From preoperative period to seven years postoperatively, patient-reported outcomes improved ( p < 0.001), including mean NDI (by 45.9%), the Veterans Rand 12-item Health Survey (by 54.1%), and mental component summary (by 41.85%), with an 88% patient satisfaction rate [ 1 ]. Furthermore, Buttacavoli et al retrospectively reviewed 43 patients treated for three-level disc degenerative disease, comparing those who were given artificial disc (ProDisc-L) or circumferential fusion.…”
Section: Reviewmentioning
confidence: 99%
“…Anterior cervical discectomy and fusion (ACDF) has historically been the gold standard for treating degenerative disc disease (DDD) in the cervical spine. However, more recently, cervical disc arthroplasty (CDA) has become more prominent as an alternative to ACDF for treating cervical DDD due to its ability to preserve segmental motion and decrease the risk of adjacent disc disease along with nerve root compression [ 1 ]. Long-term clinical studies on single-level treatments have even demonstrated superior clinical outcomes for CDA when compared with ACDF [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation